FINANCIAL PERFORMANCE ANALYSIS USING THE DU PONT METHOD AT PT. JASA ARMADA INDONESIA Tbk 2017-2021 PERIOD - Nida Nusaibatul Adawiyah; Cicilia Erly Istia; Mufid Suryani; Risa Septiani (Jurnal Ekonomi, 2022)
The development of technology and the flow of information that is increasingly sophisticated and modern have led to the rapid development of the business world. Transportation is a very important means of supporting the successful development of a country, especially in supporting community economic activities. This study aims to determine the financial condition of PT. Jasa Armada Indonesia Tbk for the 2017-2021 period by analyzing its financial statements using the Du Pont, which consists of Net Profit Margin, Total Asset Turnover, Return on Investment, Equity Multiplier, and Return on Equity. The type of data used in this research is quantitative data. Sampling in this study uses purposive sampling. The results of the research show that PT. Jasa Armada Indonesia Tbk has a Net Profit Margin, Total Asset Turnover, Return on Investment, Equity Multiplier, and Return on Equity with good results, namely above the average value so the company's financial performance is good in the 2017-2021 period